Research of the Hydraulic Shift Characteristic of Engineering Vehicle Gearbox - Zhang Hongqiang; Tian Jinyue; Chen Zhiling; Xu Gang; Zhou Ping (Jixie chuandong)
Taking the 200 k W power-shift engineering vehicle gearbox as research object,the general analysis of the gearbox is carried out.The simulation models of hydraulic control system and dynamic test of gearbox are constructed by utilizing AMESim software.The hydraulic control system performance characteristic curves of gearbox are obtained by applying parameterization to the simulation model.The rationality and stability of the hydraulic controlling system are verified through the performance characteristic curves,some valuable references to optimize control strategy and improve shift quality are provided.